2019
DOI: 10.3389/fimmu.2019.02028
|View full text |Cite
|
Sign up to set email alerts
|

More Than Suppression: Glucocorticoid Action on Monocytes and Macrophages

Abstract: Uncontrolled inflammation is a leading cause of many clinically relevant diseases. Current therapeutic strategies focus mainly on immunosuppression rather than on the mechanisms of inflammatory resolution. Glucocorticoids (GCs) are still the most widely used anti-inflammatory drugs. GCs affect most immune cells but there is growing evidence for cell type specific mechanisms. Different subtypes of monocytes and macrophages play a pivotal role both in generation as well as resolution of inflammation. Activation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
128
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(143 citation statements)
references
References 163 publications
(248 reference statements)
10
128
0
5
Order By: Relevance
“…(27,29,35,67,82)), we demonstrate that inflammation and MΦs/µglia are required for RPE regeneration in vivo. Synthetic GCs, such as dexamethasone, have been widely used to suppress inflammation and do so by attenuating the inflammatory phase post-injury and driving macrophages toward an anti-inflammatory phenotype (87)(88)(89). Results from our study support the existence of a critical inflammatory phase during RPE regeneration, as evidenced by expression of phagocytic (e.g.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…(27,29,35,67,82)), we demonstrate that inflammation and MΦs/µglia are required for RPE regeneration in vivo. Synthetic GCs, such as dexamethasone, have been widely used to suppress inflammation and do so by attenuating the inflammatory phase post-injury and driving macrophages toward an anti-inflammatory phenotype (87)(88)(89). Results from our study support the existence of a critical inflammatory phase during RPE regeneration, as evidenced by expression of phagocytic (e.g.…”
Section: Discussionsupporting
confidence: 72%
“…MΦ/µglia infiltration was unaffected and pyknotic nuclei did not accumulate in dexamethasone-treated larvae, indicating intact phagocytic function, yet the outcome was still impaired RPE regeneration. GCs have been shown to have varying effects on macrophage migration (89); indeed, in GC-treated zebrafish post-wounding, leukocyte migration defects have been detected in some injury paradigms (27,35,67), but not others (90,91). Further, GCs have been shown to increase phagocytosis by macrophages to promote expedited resolution of inflammation (87,89), which may explain the lack of pyknotic nuclei accumulation in dexamethasone-treated larvae post-RPE damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GCs remove endo-and exogenous danger signals by an increased phagocytic capacity, and limit T-cell activation [25].…”
Section: Discussionmentioning
confidence: 99%
“…The recent evidence revealed that GCs could e ciently inhibit these processes by downregulating pro-in ammatory mediators from macrophages and monocytes and their migration toward in ammatory stimuli. In addition, GCs could remove endo-and exogenous danger signals by increasing phagocytic capacity and limiting T-cell activation [25].…”
Section: Discussionmentioning
confidence: 99%